Odpowiedzi

2010-04-14T19:46:42+02:00
Rozwiąż równania
y(2y-1) = 2(2+y)²
2y²-y=2(4+y²+4y)
2y²-y=8+2y²+8y
2y²-y-2y²-8y=8
-9y=8 |:(-9)
y=-8/9

(½x-4)² = (½x+4)²
1/4x²-8*1/2x+16=1/4x²+8*1/2x+16
1/4x²-4x-1/4x²-4x=16-16
-8x=0 |:(-8)
x=0

(√3y+ 2)²-(√3y+2)(√3y-2)=0
3y+4√3y+4-[(√3y)²-4]=0
3y+4√3y+4-3y+4=0
4√3y=-8 |:4√3
y=-8/4√3
y=-8√3/4*3
y=-8√3/12
y=-2√3/3
2010-04-14T19:56:10+02:00
1.
2y²-y=2(4+y²)
2y²+y=8+2y²
2y²-2y²+y=8
y=8

2.
(½x-4)² = (½x+4)²
¼x²-16=¼x²+16
¼x²-¼x²=16+16
0=32 równanie sprzeczne

3.
tu trzeba skorzystać ze wzorów skróconego mnożenia
(√3y+ 2)²-(√3y+2)(√3y-2)=0
√3y²+2*√3y*2²-√3y²-2²=0
3y²+8√3-3y²-4=0
3y²-3y²+8√3=0
8√3=0
2010-04-14T20:05:56+02:00
A)y(2y-1)=2(2+y)²
2y²-y=2(4+4y+y²)
2y²-y=8+8y+2y²
-y=8+8y
-y-8y=8
-9y=8/:(-9)
y=-⁸₉(ułamek)

b)(½x-4)² = (½x+4)²
¼x²-4x+16=¼x²+4x+16
-4x=4x
-4x-4x=0
-8x=0
x=0

c)(√3y+ 2)²-(√3y+2)(√3y-2)=0
3y+4√3y+4-3y-2√3y+2√3y-4=0
4√3y=0/:4√3
y=0
prosze...;)